Avaliação de concordância entre instrumentos móveis para a verificação de variabilidade da frequência cardíaca - SILVA, Thyago Martins Viana da (2022)
The aim of the present study was to investigate the agreement in heart rate variability domain methods of the ELITE HRV mobile app together with the Polar® heart monitor (V800) + Kubius HRV 3.3.1 software, both associated with a chest strap (H10). Participated in the study 40 individuals, 23 males and 17 females, with a mean age of 24 ± 5 years, height 1.7 ± 0.03 meters, body mass 60 ± 10 kilograms and BMI 19 ± 2. This study is characterized as quantitative and applied in a transversal way. For data collection, this research had only one meeting, where the study subjects were instructed to remain in a stabilized sitting position for about five minutes to perform the measurement on the instruments, that is, five minutes using the cardiac transmitter (H10) with tracking and data storage via Polar® heart monitor (V800) and then the same equivalent period for the ELITE HRV app. From this, the following variables were collected: SDNN (standard deviation between normal to normal intervals) and RMSSD (the square root of the mean differences of successive NN intervals). To carry out the analysis, two statistical coefficients were selected, Person's correlation and the intraclass correlation intended for intra-instrument evaluations. In conclusion, when compared with a valid measure such as the Polar® heart monitor (V800), the APP Elite HRV presented excellent and moderate agreement values for the analyzed variables (RMSSD and SDNN) which may encourage the recommendation to use this associated instrument with other validated parameters.